Building the Science to Guide Nursing Administration and Leadership Decision Making. (January 2022) - Joseph, M. Lindell; Nelson-Brantley, Heather V.; Caramanica, Laura; Lyman, Bret; Frank, Betsy; Hand, Mikel W.; Parchment, Joy; Ward, Danielle M.; Weatherford, Barbara; Chipps, Esther
Abstract : OBJECTIVE: The aim of this study was to identify the challenges, barriers, and solutions for conducting nursing administration and leadership science (NALS) research. BACKGROUND: Evidence from leadership science should be at the forefront of nurse leaders' decision making. Yet, challenges remain in building the evidence and moving it into nursing administration and leadership practice. METHODS: This study used a Delphi technique with open-ended questions and direct content analysis to evaluate survey responses of members of the Association for Leadership Science in Nursing and American Organization for Nursing Leadership. RESULTS: Open-ended responses were coded to yield super categories and supportive codes for areas with limited evidence to guide leadership practice and the challenges for conducting NALS research. CONCLUSIONS: These findings provide future directions for continuously driving NALS research and for building and leveraging leadership science to support nursing administration decision making.